Prognostic value of ERCC1 and ERCC2 gene polymorphisms in patients with gastric cancer receiving platinum-based chemotherapy - Mo, Juanmei (Int J Clin Exp Pathol, 2015)
We conducted a prospective study to analyze whether ERCC1 rs11615 and rs3212986 and ERCC2 rs13181 and rs1799793 gene polymorphisms could serve as potential biomarkers for the prognosis of gastric cancer. A total of 228 patients with pathologically proven gastric cancer and receiving platinum-based chemotherapy were recruited from our hospital between October 2009 and October 2011. The ERCC1 rs11615 and rs3212986 and ERCC2 rs13181 and rs1799793 polymorphisms were genotyped using the polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) assay. Conditional logistic regression analysis revealed that patients carrying the CA and AA genotypes of ERCC1 rs3212986 polymorphism showed a poorer response to chemotherapy compared to the CC genotype (CA vs. CC: OR = 0.28, 95% CI = 0.06-0.98, P = 0.04; AA vs. CC: OR = 0.49, 95% CI = 0.06-0.98, P = 0.01). Moreover, the CA+AA genotype of ERCC1 rs3212986 polymorphism showed a significantly poorer response to chemotherapy (CA+AA vs. CC: OR = 0.49, 95% CI = 0.27-0.90). Patients with the AA genotype of ERCC1 rs3212986 polymorphism had a longer overall survival time when compared with the CC genotype (34.91 months vs. 51.19 months, log-rank P = 0.003). The AA genotype of ERCC1 rs3212986 polymorphism in gastric cancer patients was correlated with a higher risk of death from varying causes by the Cox proportional hazards model, compared to the CC genotype (HR = 6.19, 95% CI = 1.42-30.60). In conclusion, the ERCC1 rs3212986 polymorphism was found to influence the response to chemotherapy and overall survival of gastric cancer patients.